The innovation tournament handbook a step-by-step guide to finding exceptional solutions to any challenge - Terwiesch, Christian; Ulrich, Karl T. (Wharton School Press, 2023)
What new products or services should you launch next year? How can you improve the productivity of a paint line? What should you name your new venture? How can you decrease patient waiting times? How can you improve the customer experience?Pretty much any creative problem-solving task can be framed as seeking a new match between solution and need, from operational process improvements to creating strategies to foster organic growth. Innovation tournaments aim to find a match that is not just good, but exceptional.Leveraging more than two decades of experience organizing innovation tournaments in Silicon Valley and on Wall Street, from Buenos Aires to Kuwait City, Shanghai to Moscow, and with many Fortune 500 companies, two renowned researchers, entrepreneurs, and the foremost experts on innovation tournaments offer a template that you can use to generate winning ideas that will drive great outcomes-whatever your challenges, whatever your business.In The Innovation Tournament Handbook: A Step-by-Step Guide to Finding Exceptional Solutions to Any Challenge, Wharton professors Christian Terwiesch and Karl T. Ulrich offer an engaging, often humorous, and always actionable guide to help you learn:--How to frame and articulate your specific innovation challenge--How to decide on the right format, structure, and strategic direction for your own innovation tournament--How to maximize the quality of the opportunities that will compete--How to select the very best ideas--How to develop those ideas into real-world opportunities--How to use tournaments to foster a culture of innovationFast-reading and filled with real-world successes, The Innovation Tournament Handbook is a comprehensive roadmap to finding a new match between a solution and a need that is not merely good, but exceptional.
Keywords: Decision making; Problem solving